Diet influences metabolic rates in neotropical birds (2020)
Metabolic rates are an important physiological metric because they serve as proxies for the energy that organisms need to survive. Metabolic rates are affected by intrinsic characteristics of organisms and by environmental factors. For instance, diet may affect metabolic rates due to differences in energy contents and digestibility of food items. Here we assess whether metabolic rates are associated with diet in Neotropical birds. Between June 2017 and November 2018, we measured three components of metabolic rates (basal, maximum, and aerobic scope) for 118 individuals from 28 species in three localities in Valle del Cauca, Colombia located in lowlands (800 m and 1000 m) and highlands (2400 m). For each species, we also obtained the percentage of fruit and invertebrates in their diets from the literature. We used phylogenetically corrected linear models to examine relations between diet, metabolic rates, and elevation. We found that birds from higher elevations had higher metabolic rates than those from lower elevations. Also, basal metabolic rate (at all elevations), as well as maximum metabolic rate and aerobic scope in lower elevations, were lower in species that eat more fruit. Maximum metabolic rate and aerobic scope in high elevations did not vary with diet. These patterns may be related with compound digestibility, absorption of energy, and the different challenges of living at high elevations (e.g thermoregulation). Our study helps to understand different ecological factors that affect the physiology of Neotropical birds, and the importance of energetic constraints for different life- history traits in birds.